Efektivitas layanan bimbingan dan konseling untuk meningkatkan pemahaman pentingnya melanjutkan pendidikan ke perguruan tinggi - Nikmarijal, Nikmarijal; Ahmad, Bukhari (Jurnal Konseling dan Pendidikan, 2023)
Education will result in changes towards progress, as well as the insight and ability to plan and prepare for a better life. The research objective is to examine the effectiveness of guidance and counseling services in developing student comprehension of the importance of continuing education in higher education. The sample in this study is 100 students in senior high school. This research employed a quantitative approach using a quasi-experimental design and a pretest-posttest model. The descriptive statistics table revealed the pretest and posttest results, with an average score of 60.74 on the pretest and 84.07 on the posttest. According to calculations using the Wilcoxon signed rank test, we obtained a Z value of -8.684 with Asyim. The Sig 2 tailed value is 0.000, falling below 0.05, indicating a significant difference between the pre-test and post-test in the research group. The experimental group's posttest results revealed changes in the students